The effect of administering ethanolic extract of red lotus stem (nymphaea rubra) on blood sugar levels of mice (mus musculus) - Fitri Nuroini; Suci Zahra Salsabila; Ragil Saptaningtyas; Andri Suksesi (Universitas Gadjah Mada, 2026)
Metformin, a drug commonly used by patients with diabetes, is known to have major side effects in the form of gastrointestinal intolerance, including bloating, discomfort, diarrhea, and lactic acidosis. Long-term use of metformin (>2 years) may also increase the risk of developing diabetic neuropathy by up to four times. The presence of these side effects calls for natural alternatives with lower risk, one of which is red lotus stem extract (Nymphaea rubra). The compounds contained in red lotus stem extract, such as vitamin C, minerals, phenolic compounds, and flavonoids, are known to have antidiabetic potential. This study aimed to determine the effect of Ethanolic extract of red lotus stem (Nymphaea rubra) on the blood sugar levels of mice (Mus musculus). The research subjects consisted of 25 male white mice (Mus musculus) weighing approximately ±35 g and aged 16 weeks, divided into 5 treatment groups with 5 replications. The mice were induced with alloxan at a dose of 90 mg/kgBW through a single intraperitoneal (i.p.) injection, followed by oral administration of Ethanolic extract of red lotus stem at doses of 200 mg/kgBW and 400 mg/kgBW for 14 days. Blood sugar levels were measured before alloxan induction, after induction, and 14 days after treatment using a spectrophotometer with the GOD-PAP (Glucose Oxidase-Peroxidase Aminoantipyrine) method. The results showed that the average blood sugar levels in groups P1 (200 mg/dL) and P2 (400 mg/dL) were 171.00 mg/dL (hyperglycemia) and 105.00 mg/dL (normal), respectively. Based on the percentage reduction in blood sugar levels, group T1 showed a greater reduction of 37.64% compared with group T2 at 26.31%. In conclusion, the administration of Ethanolic extract of red lotus stem was shown to affect the reduction of blood sugar levels in mice.